2015
DOI: 10.16949/turcomat.44905
|View full text |Cite
|
Sign up to set email alerts
|

Can Technology-Assisted Instruction Improve Theoretical Awareness? The Case of Fundamental Theorem of Calculus

Abstract: Bu çalışmanın amacı, teknoloji destekli öğretimin teorik farkındalığa etkisini, yükseköğretim matematiğinin önemli teoremlerinden biri olan Analizin Temel Teoremi (ATT) bağlamında değerlendirmektir. Çoklu yöntem modeline göre yapılandırılan araştırmada, bir öğretim deneyinin etkililiği nitel veri toplama süreçleri üzerinden, var olan durum ile karşılaştırmalı olarak değerlendirilmiştir. Bir devlet üniversitesinin ilköğretim matematik öğretmenliği 2. sınıf programına kayıtlı olan 84 öğrencisi yansız atama ile i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
3
3
0
1
Order By: Relevance
“…Therefore, according to the findings of this study, although the software played a more effective role in the learning process of the students than the blackboard, the necessity of creating technologysupported content to support the learning-teaching process emerged. This necessity is similar to the research results reported by Sevimli and Delice (2015). With the help of the dialogues and her notes, the researcher teacher concluded that environments where visual elements are not used encourage students to memorize.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Therefore, according to the findings of this study, although the software played a more effective role in the learning process of the students than the blackboard, the necessity of creating technologysupported content to support the learning-teaching process emerged. This necessity is similar to the research results reported by Sevimli and Delice (2015). With the help of the dialogues and her notes, the researcher teacher concluded that environments where visual elements are not used encourage students to memorize.…”
Section: Discussionsupporting
confidence: 84%
“…within the content of mathematics. Parallel to this problem, important experience has been gained on how to use a computer so that students can learn mathematics better (Powers & Blubaugh, 2005;Pierce & Stacey, 2002;Renshaw & Taylor, 2000;Sevimli & Delice, 2015;Wiest, 2001). Many researchers stated that Dynamic Geometry Software (DGS) and Computer Algebra Systems (CAS) have a significant potential in reflecting these experiences into mathematics classes (Hazzan & Goldenberg, 1997;Powers & Blubaugh, 2005;Tabuk, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This result matches up with the findings which are situated in the literature about the positive effect of the CAMI activities on parabola subject in which various softwares such as CASs (Bos, 2007;Kutluca, 2009) and DGSs (Phonguttha et al, 2009;Ayvaz and Ozdemir, 2010) are used. Similar results have been found in the studies, in which CAS softwares have been used for lecturing different subjects and university students have taken part as participants in general (Hillel, 1993;Porzio, 1994;Cooley, 1995;Stephens and Konvalina, 1999;Aksoy, 2007;Bulut, 2009;Sevimli, 2013;Sevimli and Delice, 2015).…”
Section: Conclusion and Recommendationssupporting
confidence: 83%
“…When we examine the literature, it is understood that the teaching activities, which are carried out through CASs, effect students' conceptional comprehension levels (Ghosh, 2003;Kabaca, 2006;Aksoy, 2007;Sevimli, 2013;Sevimli and Delice, 2015) problem solving skills (Aktümen, 2007;Tuluk, 2007;Sevimli, 2013) academic achievements (Stephens and Konvalina, 1999;Aksoy, 2007;Bulut, 2009) calculational skills (Bulut, 2009;Sevimli, 2013) mathematical thinkings (Tuluk, 2007;Bulut, 2009) attitudes towards mathematics (Kabaca, 2006;Aksoy, 2007;Aktümen, 2007;Tuluk, 2007;Aktümen and Kaçar, 2008;Taşlıbeyaz, 2010) positively. Again, similar results are emphasized also in literature reviews (Lavicza, 2008;Buteau et al, 2010;Marshall et al, 2012) that mention teaching activities which are carried out through CASs.…”
Section: Figure-1 3d Graph Plotting Through Mathematicamentioning
confidence: 99%
“…CASs, which are developed as software that can make symbolic computation besides numerical computation for solving mathematical problems, have been obtained by extending standard numerical programming languages such as C, Pascal and Fortran (Aktümen, 2007). It is understood that the educational activities carried out through CASs positively affect students' levels of conceptual understanding (Aksoy, 2007;Ghosh, 2003;Kabaca, 2006;Sevimli, 2013;Sevimli & Delice, 2015), problem solving skills (Aktümen, 2007;Sevimli, 2013;Tuluk, 2007), academic achievements (Aksoy, 2007;Bulut, 2009;Stephens & Konvalina;1999), operational skills (Bulut, 2009;Sevimli, 2013), mathematical thinkings (Bulut, 2009;Tuluk, 2007) and their attitudes towards mathematics (Aksoy, 2007;Aktümen, 2007;Aktümen & Kaçar, 2008;Kabaca, 2006;Tuluk;. Likewise, similar results were emphasized in the literature reviews dealing with the teaching activities in which CASs had been used (Buteau, Marshall, Jarvis & Lavicza, 2010;Lavicza, 2008; Marshall, Buteau, Jarvis & Lavicza; 2012).…”
Section: High School Mathematics Teachers' Levels Of Achieving Technomentioning
confidence: 99%